PENGALAMAN CAREGIVER KELUARGA DALAM MERAWAT PASIEN PENYAKIT GINJAL KRONIS YANG MENJALANI TERAPI HEMODIALISIS DI RSUP SANGLAH DENPASAR - Maitra Pratiwi (Coping: Community of Publishing in Nursing, 2014)
Family caregiver play an important role in the hospitalization of chronic kidney disease (CKD) patient who is undergoing hemodialysis. This study aims to gain a profound understanding on the meaning of meaning and significance of the experience of the caregiver in taking care of the CKD patient who is undergoing hemodialysis therapy in Sanglah Hospital. This study used qualitative phenomenological descriptive method with in depth interview. Participants in this study were caregivers families with CKD who is undergoing hemodialysis therapy which were obtained by purposive sampling technique. The data collected in the form of recorded interviews and field notes were analyzed through Collaizzi technique. This study identified seven themes namely, psychological response of the caregiver, understanding of the CKD, understanding of the hemodialysis, efforts made by the caregiver, the changes experienced by caregivers, support for the caregiver, and the caregiver expectations. The family caregiver who took care of the CKD patient whit hemodialysis therapy could utilize the available support resources both within and outside the family system, that can help the process of family solving problems.